(untitled) (Innovative professional education, 2024)
The practice of analysing the labour market and its satisfaction with the resources of vocational education and training institutions by the methodological service of vocational education and training in the Dnipro region is highlighted. Attempts to respond to the situation under martial law by using modern operational actions by educational institutions are demonstrated. The factors hindering the efficiency of actions under martial law to meet the needs of employers are listed. The list of problems to be solved in solving the problems of the current economy is formed.